Quality of service (QOS) between IPv4 and IPv6 on MPLS linux platform / Nor Asyikin Abu Bakar - Abu Bakar, Nor Asyikin (Faculty of Information Technology and Quantitative Sciences, 2006)
This research is all about performing evaluation of QoS between IPv4 and IPv6 with MPLS Linux tunneling method. IPv6, the next generation IP protocol is developed in order to overcome the shortage address experienced by IPv4 address space. IPv4 and IPv6 must be able to communicate in order to transport the IPv6 data stream over IPv4 network. Tunneling mechanism which is MPLS Linux tunneling is being used in order to transport the IPv6 data stream. Transporting IPv6 data over IPv4 network however deals with QoS issues which emphasize on the reliability and deliverable of data from source to destination. The main purpose of this research is to analyze both IPv4 and IPv6 QoS performance on top of MPLS platform in experimental environment using open source software. The next aim of the research is to compare the performance between IPv4 and IPv6 on top of MPLS platform. This research is done using a simulation of core network acting as the real core network environment. Some QoS metrics such as jitter, datagram loss, transfer rate and bandwidth will be measured using a benchmarking tool. The research conducted a quality of service measurement between both IPv4 and IPv6 on MPLS tunneling platform in order to evaluate the fair measurement performance.